EVENT-DRIVEN MANAGEMENT OF ECONOMICS AND THE EXIT OF ECONOMICS FROM STAGNATION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The work describes the developed cortege and mathematical model for managing the quality of development and exit of the system from stagnation. The scientific problem of economics  development is formulated on the basis of artificial intelligence, algebra of logic and logical-probabilistic calculus.